Hoạt động đào tạo giáo viên trước tác động của công nghệ tại Trường Đại học Công nghệ Kỹ thuật Thành phố Hồ Chí Minh: Thực trạng và đề xuất giải pháp - Phan Thị Thanh Tùng, Phan Thị Thanh Tùng; Bùi Văn Hồng, Bùi Văn Hồng (Tạp chí Giáo dục, 2026)
In the context of technological development today, technology applications in teaching and training have become rich and diverse, creating many advantages in learning for students and in teaching for lecturers. However, this impact also creates significant challenges in exploiting and managing current technology applications, especially in teacher training. This article focuses on analyzing the impact of technology on the learning needs and teaching competence requirements of teachers, the current status of technology application in teacher training, and the advantages and challenges at Ho Chi Minh City University of Technology and Engineering. From there, the article proposes measures to train teachers to adapt to the impact of technology. The results of the article can serve as a reference for students, lecturers, and researchers in the field of teacher training.